PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAME TURNAMENT PADA PELAJARAN FIKIH DI KELAS IX MTsN 11 AGAM - Lidia Marjalena; Ulva Rahmi; Kundlori Kundlori (JIP: Jurnal Ilmu Pendidikan, 2023)
This research is a qualitative study which aims to increase students’ learning motivation by using a team game tournament (TGT) type coopperative learning model in broadcast material fiqh lessons in class IX MTsN 11 Agam. The description of the focus in this research are class IXA MTsN students 11 Agam 2023/2024 academic year, totaling 25 people. The data analysis technique used is a qualitative data analysis technique. The observation results of the use of the team game tournament type cooperative learning model in learning fiqh seem to be very active. Students are actively involved in learning and collaborate well. They feel motivated to understand the fiqh (khiyar) material well because there is an element of competition in this model. In addition to the TGT model allowing teachers to focus on each team specifically, students alse have clear responsibilities within their teams which helps in the development of social and cooperative skills.